Pemuda pada Masa Pendudukan Jepang di Jawa: Semiotika Sampul Depan Djawa Baroe 1943-1945 - Noveri Faikar Urfan (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2022)
This study aims to determine the framing of the government's appeal related to Covid-19 by online news sites. It is important and interesting to study because ideally online news sites play a major role in disseminating government policies in the context of health communication to the public through their news. But in reality, at the beginning of the pandemic, reporting on online news sites actually caused an infodemic. For this reason, this research takes the period from March to July 2020 which is the initial phase of the pandemic period in Indonesia as well as the initial period of issuing government appeals related to Covid-19. This study chose Kompas.com and Tempo.co as research subjects with consideration of their credibility as trusted news sites so far in Indonesia. The method used is framing analysis with Pan and Kosicki devices in order to obtain a comprehensive analysis related to the structure of the news. The research findings result in differences in the framing of government appeals between the two news sites. Kompas.com focuses on reporting by prioritizing the educational function to support government performance. So they chose to explore the how element in the news packaging. On the other hand, Tempo.co focuses on news that carries an informative function to carry out its role as social control over government performance. For this reason, Tempo.co packs more of a why element in its reporting. However, the research findings show that framing the government's appeal about COVID-19 is useful in building health and risk information that is important as a source of information and risk mitigation.